2019
DOI: 10.1017/s2040174419000564
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to placental insufficiency alters postnatal growth trajectory in extremely low birth weight infants

Abstract: AbstractGrowth in the immediate postnatal period for extremely low birth weight (ELBW, birth weight < 1000 g) infants is an important topic in neonatal medicine. The goal is to ensure adequate postnatal growth and to minimize complications resulting from suboptimal growth. Past efforts have focused on postnatal nutrition as well as on minimizing comorbidities. It has not been systematically assessed whether antenatal factors play a role in postnatal growth. In this report, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
(52 reference statements)
0
8
0
1
Order By: Relevance
“…Additionally, placental insufficiency causes a large proportion of intrauterine growth restriction leading to birth wasting, and rapid WLZ gain after may reflect true recovery to a child’s growth potential after this constraint is removed. 35, 36 Consistent with larger WLZ increases during recovery from wasting among younger children, a larger proportion of children recovered within 30, 60, and 90 days if the wasting episode occurred before 6 months of age (Fig 3d). Younger children had more variable WLZ (SD: 0.81 <6 months, 0.54 from 6-24 months) and shorter wasting episodes (Extended Data Fig 9).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Additionally, placental insufficiency causes a large proportion of intrauterine growth restriction leading to birth wasting, and rapid WLZ gain after may reflect true recovery to a child’s growth potential after this constraint is removed. 35, 36 Consistent with larger WLZ increases during recovery from wasting among younger children, a larger proportion of children recovered within 30, 60, and 90 days if the wasting episode occurred before 6 months of age (Fig 3d). Younger children had more variable WLZ (SD: 0.81 <6 months, 0.54 from 6-24 months) and shorter wasting episodes (Extended Data Fig 9).…”
Section: Introductionmentioning
confidence: 60%
“…Seasonal food insecurity coincides with peak energy demands during agricultural work periods, which in turn leads to undernutrition among pregnant and lactating mothers and their children. 17, 36, 51 Women working in agriculture often have less time to spend with their children, which can reduce breastfeeding frequency and can result in early morning preparation of weaning foods that become contaminated in hot, humid conditions. 53, 54 Weather-driven seasonal increases in infectious disease transmission could also play a role in seasonal wasting, but the effect would vary spatially and temporally and would not fully explain the consistent patterns observed here.…”
Section: Discussionmentioning
confidence: 99%
“…However, in such case, fetal reprogramming likely has already occurred, and therefore the associated short-term and long-term adverse outcomes (e.g., neurodevelopmental abnormalities and cardiometabolic risks) may have already become irreversible. Indeed, a recent study suggested that exposure to placental insufficiency by itself was sufficient to significantly alter postnatal growth trajectories, likely due to fetal reprogramming ( 10 ). Therefore, it is very likely that the developmental trajectory of the fetus is already altered and compromised when IUGR becomes detectable clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the absence or presence of maternal preeclampsia and placental insufficiency, E/VPNs were assigned to one of the three groups for comparison: [1] no maternal preeclampsia or placental insufficiency (the non-PE/PI group); [2] maternal preeclampsia but no placental insufficiency (the PE group); and [3] placental insufficiency (the PI group). Maternal preeclampsia diagnosis was based on maternal chart review, and placental insufficiency in this study was defined as abnormal UA blood flow, including a pulsatility index of >95%, absent end-diastolic flow, or reversed end-diastolic flow ( 8 , 10 ). The grouping strategy was based solely on chart review of maternal diagnosis and the most recent umbilical Doppler findings prior to delivery without further considering underlying etiologies (e.g., TORCH infections, maternal smoking, pre-existing maternal hypertension, etc.).…”
Section: Methodsmentioning
confidence: 99%
“… 105 Since the placenta provides nutrients and oxygen to the developing fetus via the maternal blood supply, any reduction in the placenta’s blood flow and perfusion may result in FGR. 106 , 107 To improve clinical diagnostic capabilities for FGR and better understand placental function, several studies have used specialized MRI techniques to investigate normal and abnormal perfusion across placental compartments and assess microstructure and microvasculature. These techniques include diffusion-weighted imaging (DWI), diffusion tensor imaging (DTI), intravoxel incoherent motion (IVIM), arterial spin-labeling (ASL), and phase-contrast MRI (PC-MRI).…”
Section: Diffusion Perfusion and Flowmentioning
confidence: 99%